2007
DOI: 10.1016/j.smallrumres.2006.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some etiological factors predisposing to diarrhoea in lambs in “La Serena” (Southwest Spain)

Abstract: This study compares some etiological factors involved in the naturally occurrence of lamb scours in 18 Merino sheep farms randomly selected in the area of "La Serena" (Southwest Spain).A lack of influence of some variables (flock size, type of facilities, type of breeding, lambing percentage, isolation of Campylobacter jejuni, Rotavirus spp., Coronavirus spp. and Salmonella spp.) on lamb mortality rate was detected. The opposite was true for cleaning of the lambing areas, organization of lambing periods, accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 3 publications
3
8
0
1
Order By: Relevance
“…In addition, positive correlations were found between the individual values of IgG and TP in ewes before lambing. These results were in agreement with that of Andres et al [17] . Therefore, measuring serum IgG or TP in ewes before lambing would be a valuable indicator of the risk of lamb diseases or passive immunity.…”
Section: Gökçe Ataki̇şi̇supporting
confidence: 94%
See 3 more Smart Citations
“…In addition, positive correlations were found between the individual values of IgG and TP in ewes before lambing. These results were in agreement with that of Andres et al [17] . Therefore, measuring serum IgG or TP in ewes before lambing would be a valuable indicator of the risk of lamb diseases or passive immunity.…”
Section: Gökçe Ataki̇şi̇supporting
confidence: 94%
“…This was accordance with previous studies [14,15] . Some studies considered that lambs with STPC-24 of less than 50 g/L [15] or 58 g/L [17] to be hypogammaglobulinemic and claimed that the risk of death in those lambs was high. Our study indicated that STPC-24 of 45 g/L or less could be a threshold that increases the risk of mortality in the neonatal period as 10 of the 13 lambs died in the neonatal period had STPC-24 ≤45 g/L.…”
Section: Gökçe Ataki̇şi̇mentioning
confidence: 99%
See 2 more Smart Citations
“…Neonatal enteritis in goat kids and lambs 21 days of age, or younger, is one of the most common diseases causing high morbidity and mortality in these animals [2,10,14]. The impaired growth of neonatal goat kids and lambs afflicted with enteritis, the expenditures involved in treating these animals, and their increased mortality all have costly economic losses [2,10]. Rotaviruses, adenoviruses, herpes viruses, and coronaviruses appear to be the most common viruses that cause enteritis in humans and animals [14,15].…”
Section: Introductionmentioning
confidence: 99%